1996
DOI: 10.1029/95jd03356
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric sulfur cycling in the tropical Pacific marine boundary layer (12°S, 135°W): A comparison of field data and model results: 1. Dimethylsulfide

Abstract: Shipboard measurements of atmospheric and seawater DMS were made at 12°S, 135°W for 6 days during March 1992. The mean seawater DMS concentration during this period was 4.1 ± 0.45 nM (1σ, n = 260) and the mean atmospheric DMS mole fraction was 453 ± 93 pmol mol−1 (1σ, n = 843). Consistent atmospheric diel cycles were observed, with a nighttime maximum and daytime minimum and an amplitude of approximately 85 pmol mol−1. Photochemical box model calculations were made to test the sensitivity of atmospheric DMS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 66 publications
5
44
0
Order By: Relevance
“…They state that 3 pptv of BrO prescribed during daytime could resolve the discrepancy. Similar problems with too strong measured diurnal variation of DMS compared to model calculations with standard chemistry were also found by Yvon et al (1996). Box model calculations based on recent kinetic data emphasize the possible strong effects of BrO on DMS and DMSO concentrations (Ingham et al, 1999).…”
Section: European Geosciences Union 2003 Boucher Et Al: Sensitivitmentioning
confidence: 72%
“…They state that 3 pptv of BrO prescribed during daytime could resolve the discrepancy. Similar problems with too strong measured diurnal variation of DMS compared to model calculations with standard chemistry were also found by Yvon et al (1996). Box model calculations based on recent kinetic data emphasize the possible strong effects of BrO on DMS and DMSO concentrations (Ingham et al, 1999).…”
Section: European Geosciences Union 2003 Boucher Et Al: Sensitivitmentioning
confidence: 72%
“…The flux and mean SO 2 observations from the lowest legs (<50 m, n=61) of PASE result in an average v dep just under 0.4 cm s −1 for 10 m winds ranging from 4.5 to 10 ms −1 . Standard modeling approaches tend to assign somewhat larger v dep over the ocean between 0.5 and 1.1 cm s −1 (Langner and Rodhe 1991;Pham et al 1995;Yvon et al 1996;Karl et al 2007). …”
Section: Dry Depositionmentioning
confidence: 99%
“…Yet even a clear correlation with the primary oxidation product, SO 2 , has been observed only intermittently. The early studies of Bandy et al (1992), Huebert et al (1993), and Yvon et al (1996) in the marine boundary layer (MBL) found minimal relationship between the two species on diurnal time scales, leading to considerable confusion about the source of SO 2 and non-sea salt (NSS) sulfate in remote maritime regions. Seasonal and day-to-day variations observed at Amsterdam Island in the Southern Indian Ocean did exhibit some positive correlations (Putaud et al 1992) confirming the suspicion that SO 2 , with an expected lifetime of only a couple of days, should be linked to DMS far from anthropogenic, or volcanic, sources.…”
Section: Introductionmentioning
confidence: 99%
“…[Stull, 1988]. Elevated values of"h" have primarily been used to deal with the problem of how to evaluate the flux associated with DMS that has mixed into the BuL or even the lower free troposphere [Yvon et al, 1996]. The BuL is a zone in the lower troposphere that Russell et al [1998] have recently described as defining a region of intermittent turbulence.…”
Section: Introductionmentioning
confidence: 99%